Teaching and learning english for reading at a distance on edmodo: students perception of distance teaching - Onodera, Jorge; Araújo, Aryadne Bezerra (The ESPecialist, 2023)
This article presents a perception report of distance learning in an English for reading course designed to meet the needs of the State University of Santa Cruz (UESC) employees. We seek to highlight the stutends’ perceptions regarding their learning of reading skill in English through a distance learning course. We reflect on those perceptions based on Almeida (2003), White (2003 ) and Lima (2011) with regard to distance teaching and learning. In order to properly analyze the students’ feedback, we discuss the premises of distance education, the aspects of teaching-learning process that nowadays is mediated by Digital Information and Communication Technology and some relevant issues involved in digital didactic material in teaching reading in English. The participants’ perceptions we collected through interviews and questionnaires shed light on the potential contribution of distance learning and digital technologies to the teaching-learning process of reading in a foreign language, not only in a pandemic current scenario in which physical distance became urgent.